Mosaic Structure of GaN Film Grown on Sapphire Substrate by AP-MOCVD: Impact of Thermal Annealing on the Tilt and Twist Angles - J. Laifi; M. F. Hasaneen; H. Bouazizi; Fatimah Hafiz Alsahli; T. A. Lafford; A. Bchetnia (Crystals)
A GaN layer with a thickness of 2 µm was grown on a sapphire substrate using atmospheric pressure metal–organic chemical vapor deposition (AP-MOCVD). Subsequently, the layer was annealed under a nitrogen atmosphere at temperatures ranging from 1000 °C to 1120 °C. High-resolution X-ray diffraction (HRXRD) analysis reveals the impact of thermal annealing on the mosaic structure of the GaN, specifically the tilt and twist variations in four planes: (00.2), (10.3), (10.2), and (10.1). Interestingly, the observed trends suggest a differential effect of annealing on screw and edge dislocation densities. The annealing process reduces the edge and screw dislocation density. Lower values (Dscrew = 1.2 × 108 cm−2; Dedge = 1.6 × 109 cm−2) were obtained for the sample annealed at 1050 °C. Notably, both tilt and twist angles exhibited a minimum at 1050 °C (tilt = 252 arcsecs, and twist = 558 arcsecs), indicating improved crystal quality at this specific temperature. Photoluminescence (PL) spectroscopy further complemented the structural analysis. The intensity and broadening of the yellow band (YL) in the PL spectra progressively increased with the increasing annealing temperature, suggesting the presence of additional defect states. The near band edge PL emission (3.35 and 3.41 eV) variation upon thermal annealing was correlated with the mosaic structure evolution.